Sketch-based Interfaces and Modeling - Jorge, Joaquim; Samavati, Faramarz (Springer London : Imprint: Springer, 2011)
The field of sketch-based interfaces and modeling (SBIM) focuses on developing methods and techniques to enable users to interact with a computer through sketching - a simple, yet highly expressive medium. SBIM blends concepts from computer graphics, human-computer interaction, artificial intelligence, and machine learning. Recent improvements in hardware, coupled with new machine learning techniques for more accurate recognition, and more robust depth inferencing techniques for sketch-based modeling, have resulted in an explosion of both sketch-based interfaces and pen-based computing devices. Presenting the first coherent, unified overview of SBIM, this unique text/reference bridges the two complementary research areas of user interaction (sketch-based interfaces), and graphical modeling and construction (sketch-based modeling). The book discusses the state of the art of this rapidly evolving field, with contributions from an international selection of experts. Also covered are sketch-based systems that allow the user to manipulate and edit existing data - from text, images, 3D shapes, and video - as opposed to modeling from scratch. Topics and features: Reviews pen/stylus interfaces to graphical applications that avoid reliance on user interface modes Describes systems for diagrammatic sketch recognition, mathematical sketching, and sketch-based retrieval of vector drawings Examines pen-based user interfaces for engineering and educational applications Presents a set of techniques for sketch recognition that rely strictly on spatial information Introduces the Teddy system; a pioneering sketching interface for designing free-form 3D models Investigates a range of advanced sketch-based systems for modeling and designing 3D objects, including complex contours, clothing, and hair-styles Explores methods for modeling from just a single sketch or using only a few strokes This text is an essential resource for researchers, practitioners and graduate students involved in human-factors and user interfaces, interactive computer graphics, and intelligent user interfaces and AI. Dr. Joaquim Jorge is a professor at the Computer Science and Engineering Department (DEI) of the School of Engineering (IST) at the Technical University of Lisbon, Portugal. Dr. Faramarz Samavati is an associate professor at the Department of Computer Science at the University of Calgary, Canada.